2011
DOI: 10.1161/strokeaha.110.609834
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol, Not Aspirin, Reduces Ischemic Brain Injury via Endothelial Protection in Spontaneously Hypertensive Rats

Abstract: Background and Purpose-It is well-established that hypertension leads to endothelial dysfunction in the cerebral artery.Recently, cilostazol has been used for the secondary prevention of ischemic stroke. Among antiplatelet drugs, phosphodiesterase inhibitors including cilostazol have been shown to have protective effects on endothelial cells. The aim of the present study is to investigate the effects of cilostazol and aspirin on endothelial nitric oxide synthase (eNOS) phosphorylation in the cerebral cortex, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 34 publications
(32 reference statements)
1
49
0
Order By: Relevance
“…It was shown that dipyramidol augmented the neuroprotective effects of statins in an eNOS-dependent way (Kim et al, 2008). The putative mechanism involves an increase in eNOS S1177 phosphorylation, as demonstrated in spontaneously hypertensive rats (Oyama et al, 2011) based on the reduction in postischemic brain damage following pretreatment with PDE inhibitor cilostazol. While these are the first encouraging data suggesting that PDE inhibitors can also increase eNOS activity in stroke patients (Serebruany et al, 2011), clinical use of PDE inhibitors is so far restricted to secondary prevention of ischemic stroke: Two large clinical trials (ESPRIT: European/Australasian Stroke Prevention in Reversible Ischaemia Trial (Halkes et al, 2007), ESPS-2: European Stroke Prevention Study 2 (Diener et al, 1996)) proved that dipyramidole in combination with acetylsalicylic acid (ASA) is more effective in preventing secondary ischemic insults than ASA alone.…”
Section: Phosphodiesterase Inhibitorsmentioning
confidence: 97%
“…It was shown that dipyramidol augmented the neuroprotective effects of statins in an eNOS-dependent way (Kim et al, 2008). The putative mechanism involves an increase in eNOS S1177 phosphorylation, as demonstrated in spontaneously hypertensive rats (Oyama et al, 2011) based on the reduction in postischemic brain damage following pretreatment with PDE inhibitor cilostazol. While these are the first encouraging data suggesting that PDE inhibitors can also increase eNOS activity in stroke patients (Serebruany et al, 2011), clinical use of PDE inhibitors is so far restricted to secondary prevention of ischemic stroke: Two large clinical trials (ESPRIT: European/Australasian Stroke Prevention in Reversible Ischaemia Trial (Halkes et al, 2007), ESPS-2: European Stroke Prevention Study 2 (Diener et al, 1996)) proved that dipyramidole in combination with acetylsalicylic acid (ASA) is more effective in preventing secondary ischemic insults than ASA alone.…”
Section: Phosphodiesterase Inhibitorsmentioning
confidence: 97%
“…Cilostazol (CZ), a selective inhibitor of type III phosphodiesterase in platelets or VSMCs which has antithrombotic properties [126], an inhibitory action on the progression of carotid intima-media thickness [127], and a protective action on endothelial cell functions [128], has been approved for the treatment of symptoms related to peripheral arterial occlusive disease and symptoms of intermittent claudication and for the prevention of recurrent cerebral infarction in Japan [129]. CZ prevented experimental cerebral vasospasm [130,131,132] and also reduced moderate to severe vasospasm on angiogram from 42% in controls to 15% in the treated group in humans (n = 50) [133].…”
Section: Other Antagonists Of Pdgf-bb Function For the Prevention Of mentioning
confidence: 99%
“…Cilostazol (CLS) possesses a powerful means to produce various pleiotropic effects through the elevation of intracellular cyclic adenosine monophosphate (cAMP) levels, resulting in the increased phosphorylation of the cAMP response element binding protein (CREB) [15,16,17]. CLS has been widely approved for the secondary prevention of ischemic stroke [18]. …”
Section: Introductionmentioning
confidence: 99%